The crystal - Graham, Wendy; Forss, Ian (Macmillan Education Australia South Yarra, Vic., 1997)
The Crystal by Wendy Graham is a magical adventure story that follows young protagonists as they uncover secrets and embark on a journey inspired by a mysterious crystal, exploring themes of friendship and courage.